RANCANG BANGUN APLIKASI PENGOLAHAN DATA BANK SAMPAH BERBASIS DESKTOP: (STUDI KASUS PADA RW.13 KELURAHAN DEPOK JAYA) - Audriane Zalencia Surya; Ahmad Fauzi; Andi Prastomo (CV. Denasya Smart Publisher, 2024)
Garbage is leftover material that is produced from a production process both industrial and household. Then need treatment to overcome the problems that arise from waste, one of which is the existence of a garbage bank. In processing data in a garbage bank, it is still done manually by recording it with books. Therefore, along with the rapid advancement of technology, a desktop-based system is created that can help the process of waste transactions at the garbage bank. In the process of making the system was carried out by research at the Garbage Bank RW.13, Depok City. This research uses the method of observation, data collection and interviews The results of this study using black box testing showed that the functional system was running well and was able to follow the data processing system in accordance with the processing of RW.13 waste bank data and assisted officers in serving balance checking transactions and exchanging balances into cash effectively, which is desktop based with Java programming language